Follicular Variant of Papillary Thyroid Carcinoma: Cytological Indicators of Diagnostic Value - Manimaran D (Journal of Clinical and Diagnostic Research, 2014)
Background: Fine needle aspiration cytology (FNAC) is an important investigation in preoperative diagnosis of thyroid lesions. Follicular variant of papillary carcinoma thyroid (FVPTC) is a well defined entity in histopathology, but its diagnosis in FNAC is usually missed and is challenging compared to classic papillary thyroid carcinoma. Aims: The purpose of this study is to retrospectively analyze cytological features in histologically confirmed cases of FVPTC, compare them with literature and document the features that could increase the sensitivity of FNAC diagnosis. Materials and Methods: Cytological smears from 22 histologically confirmed cases of FVPTC were evaluated for microscopic pattern and nuclear features by two independent pathologists and results compared with previous studies. Statistical analysis was done based on bivariate Pearson’s correlation coefficient. Results: Among 22 cases 21 were female and one male with age range 21 – 50 years . All patients had a solitary nodule except one with multicentric presentation. Preoperative cytological diagnosis were, classic papillary thyroid carcinoma (PTC); 7, FVPTC; 3, suspicious for PTC; 4, follicular neoplasm; 5 and adenomatous goiter;3. Diagnosis upon cytological review were, FVPTC; 11, classic PTC; 7 , suspicious for PTC; 2, follicular adenoma;1 and adenomatous goiter; 1. Conclusion: We conclude that cellular smears with features as observed in our case like microfollicular pattern, syncytial clusters, fine powdery chromatin, anisonucleosis and nucleomegaly should alert the pathologist to look carefully for other more specific features like nuclear grooves and nuclear pseudoinclusions. This approach will help in avoiding misdiagnosis of FVPTC and would aid in choosing the right treatment modality.